Students’ Perceptions and Constraints on The Use Of Quizizz in Teaching and Learning Process During Covid-19 Pandemic - I Wayan Suarnajaya; Ni Putu Astiti Pratiwi; Ni Kadek Indah Dili Yanti Indah Dili (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2021)
The purposes of this research were to (1) identify students’ perceptions about the use of Quizizz to assist the learning process during Covid-19 Pandemic; (2) find out whether there are certain constraints that the students have about the use of Quizizz to assist the learning process during Covid-19 pandemic. This study was designed in the form of mixed-method. A research design that combines qualitative and quantitative study in the process of collecting and analyzing the data is called mixed-method (creswell&Tashakkori, 2017). The research subjects were 70 participants of the third-grade students of SMA N 1 Blahbatuh in academic year 2020/2021. Data collection was conducted using a questionnaire and interview. The result of this study had shown that students’ perceptions about the use of Quizizz were very good perceptions and internet connection problems became the constraint that the students had about the use of Quizizz in a pandemic situation.